Comparison of albumin 4%, gelatine, and ringer lactate as volume expander post-resuscitative phase on cardiac output and lactate serum after Coronary Arterial Bypass Grafting (CABG) on-pump: Single-center randomized prospective study - Prieta Adriane; Ni Luh Kusuma Dewi; Ardiyan Ardiyan (Intisari Sains Medis, 2022)
Background. The use of protein colloid in fluid management post-cardiac surgery is debatable whether it is more beneficial than non-protein colloid or crystalloid. Patients who still need more volume after the resuscitative phase might benefit from optimal fluid management by choosing the most beneficial fluid. This study compared albumin 4% administration to gelatine and ringer lactate as a volume expanders post-resuscitative phase after coronary artery bypass grafting (CABG) on-pump.Methods. We conducted a single-centered, single-blind, randomized controlled study that assigned 120 patients undergoing elective CABG on-pump. Subjects who met inclusion criteria received 125 ml/hour of either albumin 4%, gelatine colloid, or Ringer's lactate (RL) as the only infusion fluid for 4 hours after the first assessment post-resuscitative phase,  after intensive care unit (ICU) admission. After fluid administration, patients were reassessed. The assessment included cardiac output and lactate serum as the primary outcome, while the duration of mechanical ventilation, ICU, and hospital stay were recorded as secondary outcomes.Results. The mean of cumulative cardiac output improvement differed between the group albumin 4% 1.18 L/min, gelatine 0.88, and RL 0.74 (p=0.002). Lactate serum decreased in the albumin 4% group as much as 3.31 gr/dl compared to gelatine 2.13 and RL group 2.37 (p=0.005). Duration of mechanical ventilation, length of stay in ICU, and hospital post-operative were shorter in the albumin group than in other groups. Conclusions. Albumin 4% used as a volume expander in the post-resuscitative phase still improved cardiac output and tissue micro-perfusion than gelatine and ringer lactate.